ChemInform Abstract: ′Pd20Sn13′ Revisited: Crystal Structure of Pd6.69Sn4.31. Issue 37 (September 2015) - Klein, Wilhelm; Jin, Hanpeng; Hlukhyy, Viktor; Faessler, Thomas F.
Abstract Single crystals of Pd6.69Sn4.31 are obtained in attempts to grow ternary alloys in the system K—Pd—Sn (Nb crucible in evacuated silica tubes, 1.